Remarkably rapid regioselective synthesis of beta-enaminones using silica chloride in a heterogeneous as well as an ionic liquid in a homogeneous medium at room temperature - Gholap, Atul R.; Chakor, N. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Molecular Catalysis A-Chemical, 2006)
{Silica chloride as a heterogeneous catalyst has been used for the regioselective synthesis of P-amino-a,P unsaturated esters and ketones. Similar regioselective synthesis was also performed using an ionic liquid 1-n-butyl imidazolium tetrafluoroborate [
Keywords: direct oxidation of H-2 to H2O2; H2O2 decomposition; H2O2 hydrogenation; Promoting action of chloride or bromide anions; supported Pd catalysts

Direct synthesis of H2O2 from H-2 and O-2 over Pd/H-beta catalyst in an aqueous acidic medium: influence of halide ions present in the catalyst or reaction medium on H2O2 formation - Samanta, Chanchal; Choudhary, Vasant R. (Catalysis Communications, 2007)
The influence of different halide ions present in the catalyst or reaction medium on the performance of Pd/H-beta catalyst in the direct H2O2 synthesis in an aqueous acidic (0.03 M H3PO4) reaction medium at 27 degrees C and atmospheric pressure has been thoroughly investigated. The results showed a strong influence of both the bulk Pd oxidation state in the catalyst and the halide ions added to the reaction medium on the performance of the catalyst in the H-2 to H2O2 oxidation, H2O2 decomposition/hydrogenation reactions. The different ammonium halides impregnated reduced Pd/H-beta catalyst calcined in inert (N-2) and oxidizing (air) gaseous atmospheres also revealed that the bulk Pd oxidation state and nature of the halide ions present in the catalyst together control the overall performance of the catalyst in the H2O2 formation reaction. The presence of halide ions in reaction medium or in the catalyst significantly changes the selectivity for H2O2 formation in the direct H2O2 synthesis. Bromide ions are found to remarkably enhance the H2O2 selectivity in the direct H2O2 synthesis irrespective of the Pd oxidation state in the catalyst. The promoting action of Br- is attributed mainly to the large decrease in the H2O2 decomposition and hydrogenation activities of the catalyst and also inhibition for the non-selective H-2-to-water oxidation over the catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: direct H2O2 synthesis; H-P supported Pd catalyst; H2O2 decomposition; H2O2 hydrogenation; promoting action of bromide ions

Direct synthesis of H2O2 from H-2 andO(2) and decomposition/hydrogenation of H2O2 in an aqueous acidic medium over halide-modified Pd/Al(2)O3 catalysts - Samanta, Chanchal; Choudhary, Vasant R. (Applied Catalysis A-General, 2007)
Direct synthesis Of H2O2 from its elements was carried out in an acidic aqueous reaction medium over halide-modified oxidized and reduced Pd/ Al2O3 catalysts under very mild conditions (at 27 degrees C and atmospheric pressure). The halide ions were introduced into the catalyst by incorporating halide ions into supported Pd/gamma-Al2O3 catalyst or via depositing halide ions on the support (gamma-Al2O3) prior to Pd deposition. The H2O2 decomposition and hydrogenation over the corresponding catalysts were also carried out under the reaction conditions similar to those employed for the H2O2 synthesis in order to elucidate the factors strongly affecting the H2O2 yield/selectivity in the direct H2O2 process. The performance of halide-modified Pd/Al2O3 catalysts in the direct H2O2 synthesis revealed that halide insertion in the catalyst system prior to or after Pd deposition on the support had comparable qualitative effect on the H2O2 formation. Both the Pd oxidation state and the nature of the halide ions had strong influences on the H-2 conversion (in direct H2O2 Synthesis process) and H2O2 decomposition and/or hydrogenation reaction. While the effect of Pd oxidation state on the H2O2 formation was significant for the catalytic system containing F- and Cl- ions, the influence of the Pd oxidation state was found less important for the catalyst system containing Br- ions; the H2O2 formation selectivity increased significantly due to the presence of Br- ions, irrespective of the Pd oxidation state. The nature of the H2O2 destruction pathway (i.e. hydrogenation and/or decomposition) in the presence of hydrogen over halide-modified Pd/Al2O3 catalysts was found to be strongly dependent upon the nature of the halide ions incorporated in the catalyst during halide-modification of the catalyst. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: direct H2O2 synthesis; H2O2 decomposition; H2O2 hydrogenation; halide-modification; Pd oxidation state

Formation from direct oxidation of H-2 and destruction by decomposition/hydrogenation of H2O2 over Pd/C catalyst in aqueous medium containing different acids and halide anions - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Direct oxidation of H-2 by O-2 to H2O2 and decomposition/hydrogenation of H2O2 (at 27 degrees C and atmospheric pressure) over Pd/C catalyst in an aqueous acidic reaction medium have been thoroughly investigated using different mineral acids (viz. 0.1 N H2SO4, H3PO4, H3BO3, HNO3, HCl, HBr or HI) and/or halide anions (viz. F-, Cl-, Br- or I-), covering their wide concentration range (0-24 mmol/dm(3)), in the reaction medium. In the absence of any externally added halide, appreciable H2O2 formation in the H2 oxidation occurred only when the medium contained HCl. However, the rates of H2O2 decomposition and hydrogenation are greatly reduced because of the presence of any acid; the influence on the H2O2 decomposition was, however, much larger for the halo acids. In the presence of acid (0.1 N H3PO4 or H2SO4), the H-2-to-H2O2 formation reaction is greatly enhanced by the externally added halide anions up to their optimum concentrations. However, above the optimum halide anion concentration, it is inhibited more than the H-2-to-water formation (parallel) reaction, causing a decrease in both the H2O2 yield and selectivity. Whereas, the H-2 conversion and H2O2 destruction activities of the catalyst are decreased continuously with increasing the halide anion (except F-) concentration. Among the halides, chloride is the best halide promoter for Pd/C catalyst in the H-2-to-H2O2 oxidation. At the optimum Cl-concentration (5.4 mmol/dm(3)), both the H-2 conversion and H2O2 yield are passed through a maximum and the H2O2 decomposition is greatly inhibited with increasing the phosphoric acid concentration. In the absence of either the chloride anions or the acid (or both) in the reaction medium, only a little or no H2O2 is formed in the H-2 oxidation and also the rate of H2O2 destruction is very fast, particularly in the presence of H-2; the rapid destruction of H2O2 is mainly due to its decomposition rather than its hydrogenation. The best H-2-to-H2O2 oxidation results are obtained at the optimum concentrations of both the acid and halide anions. In the presence of acid and chloride (or bromide) promoter, the H2O2 hydrogenation dominates the H2O2 destruction and hence the net H2O2 formation is mainly controlled by the H2O2 hydrogenation. (c) 2006 Published by Elsevier B.V.
Keywords: H2O2 decomposition; H2O2 hydrogenation; halide anion promoters; Hydrogen peroxide; oxidation of H-2-to-H2O2; Pd/C catalyst

Direct oxidation of H-2 to H2O2 over Pd/CeO2 catalyst under ambient conditions: influence of halide ions - Samanta, Chanchal; Choudhary, Vasant R. (Chemical Engineering Journal, 2008)
Direct oxidation of H-2 by O-2 to H2O2 and decomposition/hydrogenation of H2O2 have been investigated over Pd/CeO2 catalyst in presence of different halide ions. All reactions were carried out in an aqueous acidic (0.03 M H3PO4) medium at room temperature (25 degrees C) and atmospheric pressure. When different halide ions were added directly to the reaction medium or incorporated in the catalyst, the activity/selectivity of Pd/CeO2 catalyst in the H-2 to H2O2 oxidation changed significantly, depending upon the nature of the halide ions. Different ammonium halides impregnated reduced Pd/CeO2 catalyst calcined under inert (flowing nitrogen) and oxidizing (static/flowing air) gaseous atmospheres revealed that bulk oxidation state of Pd and the nature of the halide ions incorporated into the catalyst cooperatively control the activity/selectivity of catalyst in H-2 to H2O2 oxidation. Both H2O2 decomposition and hydrogenation were found to affect strongly depending upon the nature of the halide ions present in the reaction medium or in the catalyst. Among the different halides, bromide was found the most effective promoter for enhancing the H2O2 yield/selectivity in H-2 to H2O2 oxidation, irrespective of the Pd oxidation state in the catalyst. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Br- ions; H-2 to H2O2 oxidation; H2O2 decomposition; H2O2 hydrogenation; Pd/CeO2 catalyst

Direct H-2-to-H2O2 oxidation over highly active/selective Br-F-Pd/Al2O3 catalyst in aqueous acidic medium: Influence of process conditions on the H2O2 formation - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2009)
The influence of the O-2/H-2 mote ratio in the gaseous feed and also those of other reaction conditions [viz. concentration of H3PO4 (0-5 mol/dm(3)). temperature (5-50 degrees C, gas (H-2 and O-2) space velocity (5.8-23.4 h(-1)) and reaction time (0.1-8 h)] on the H2O2 formation in the H-2-to-H2O2 oxidation over the Br(1 wt%)-F(1 wt%)-Pd(5 wt%)/Al2O3 catalyst in an aqueous acidic (H3PO4) medium have been thoroughly investigated. The effects of the O-2/H-2 ratio, reaction temperature and acid concentration on the destruction of H2O2 by its decomposition and/or hydrogenation reactions over the catalyst in the acidic reaction medium have also been studied. The net H2O2 formation (H2O2 yield) over the catalyst passed through a maximum with increasing the acid concentration, the temperature or the O-2/H-2 feed ratio. However, it decreased markedly with increasing the gas space velocity or the reaction period. The H2O2 decomposition and hydrogenation activities of the catalyst increased appreciably with increasing the reaction temperature and decreased with increasing the acid concentration. The H2O2 destruction during the H-2-to-H2O2 oxidation increased with increasing the concentration of H-2 (relative to that of O-2) due to the increased H2O2 hydrogenation rate over the catalyst. The net H2O2 formation in the H-2-to-H2O2 oxidation decreased sharply with increasing the initial amount of H2O2 present in the reaction mixture. The presence of H2O2 and the higher H-2/O-2 ratios have detrimental effects on the net formation of H2O2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Br-F-Pd/Al2O3 catalyst; H2O2 decomposition; H2O2 hydrogenation; hydrogen oxidation; Hydrogen peroxide